TAREKAT SYEIKH MUHAMMAD ARSYAD AL-BANJARI: TELAAH ATAS KITAB KANZ AL-MA'RIFAH - Hadi, Abdul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
Development of Sufism in the archipelago is one icon in view of the problems connected with the Sufi. Sufism is the diversity of colour patterns of thought of religious life, while religious practice to be a representation of the diversity of religious thought to be highly variable and often decorated with the interview "controversial" a very sharp. In the context of religious institutions belonging to the tarekat also have a variety of variants, so that a diverse group of tarekat scattered every where and have the characteristics of each in accordance with religious discourse and the "religious experience" developer congregation. In fact there are some "differences" between the executive tarekat in an area with other regions, although with the same tarekat. Sheikh Muhammad Arsyad Al-Banjary as a prolific writer in various fields of Islamic sciences, such as Tawheed, Fiqh and Sufism. Among his works is the Kanz al-patterned ma'rifah Sufism, but in some discussion related to religious practices and traditions of the congregation are very close, but the Sammaniyah tarekat who had been brought closer to the Al-Banjary Arsyad not so visible in Kanz al-Ma 'rifah but Syaziliyah tarekat who are more visible.